Perfluorosulfonic acid membrane degradation in the hydrogen inlet region: A macroscopic approach. (5th January 2016) - De Moor, G.; Bas, C.; Charvin, N.; Dillet, J.; Maranzana, G.; Lottin, O.; Caqué, N.; Rossinot, E.; Flandin, L.
Abstract: This study focuses on the characterization of two complete stacks of a proton exchange membrane fuel cell that have operated in stationary mode for 12, 860 h. We compare cell voltage, and in situ and ex situ leak tests with local cell performance from a segmented cell, showing large differences in degradation between the stacks. Cells near the warmest region show more membrane degradation in the hydrogen inlets. We build a membrane thickness profile over a large area from thousands of optical microscopy images, covering seven channels and lands around the hydrogen inlet region, and identify a dramatic difference between channels 1 and 2, where dry hydrogen enters, and channel 3, where hydrogen has travelled 26 cm. Using a polytetrafluoroethylene reinforced membrane, we discriminate thickness variation for each layer and we show that degradation commences from the anode side. Highlights: Macroscopic investigation of membrane degradation in dry hydrogen inlets. In situ vs. ex situ leak tests to estimate membrane and catalysts degradation extent. Initiation of the degradation at the anode side in PTFE-reinforced PFSA membrane. Observation of degradation heterogeneities between dry and humidified channels. Degraded membrane thickness profile builds covering 7 channels/lands.